2011
DOI: 10.1007/s13277-011-0230-1
|View full text |Cite
|
Sign up to set email alerts
|

The expression of PEBP4 protein in lung squamous cell carcinoma

Abstract: The phosphatidylethanolamine-binding protein 4 (PEBP4) is a member of the PEBP family. It not only plays a role in the inhibition of the MAPK signaling pathway but also is involved in the inhibition of the JNK pathway that promotes the activation of AKT. Recent research has also shown that overexpression of PEBP4 was related to the development, invasion, and metastasis of a variety of tumors. This study aimed to investigate the correlation between PEBP4 protein expression in lung squamous cell carcinoma tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…hPEBP4 is highly expressed in several solid neoplasms such as human breast cancer, prostate cancer, colorectal cancer and lung cancer [14]–[17], but whether this is true for hematologic malignancies remains undetermined. Hence, we investigated the expression pattern of hPEBP4 in clinical specimens of normal and tumor lymph node tissue using tissue microarrays.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…hPEBP4 is highly expressed in several solid neoplasms such as human breast cancer, prostate cancer, colorectal cancer and lung cancer [14]–[17], but whether this is true for hematologic malignancies remains undetermined. Hence, we investigated the expression pattern of hPEBP4 in clinical specimens of normal and tumor lymph node tissue using tissue microarrays.…”
Section: Resultsmentioning
confidence: 99%
“…RKIP/PEBP1 is pro-apoptotic [41]–[43] while hPEBP4 is anti-apoptotic[15]–[17], [19]–[20]. Recently, RKIP has been implicated as a metastatic suppressor for prostate cancer and breast cancer [44], [45] while hPEBP4 overexprression positively corelated with the metastasis of lung squamous cell carcinomas and colorectal cancer [14], [18]. We also found silencing of hPEBP4 enhanced the the RKIP expression in the Raji cells (data now shown), indicating the regulation between the expression of RKIP and hPEBP4 via unknown mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PEBP4 has been reported to be involved in the tumor development and metastasis of various cancers [11]. For example, PEBP4 has been reported to be upregulated in pancreatic ductal adenocarcinoma (PDAC), and knockdown of PEBP4 has been shown to result in the attenuation of cancer cell growth, migration, and metastasis of PDAC cancer cells [10].…”
Section: Discussionmentioning
confidence: 99%
“…Different from other members of the PEBP family, PEBP4 contains a typical phosphatidylethanolamine‐binding domain and functions as an anti‐apoptotic protein. PEBP4 is highly expressed in various human malignancies, such as glioma, colorectal cancer, and lung cancer, playing an important role in tumor formation and progression . Our previous study revealed that PEBP4 expression is significantly upregulated in human glioma compared with normal brain tissue, and immunohistochemistry analysis indicated that PEBP4 expression is positively correlated with the tumor grade and prognosis in patients with gliomas, suggesting a possible involvement of PEBP4 in the tumorigenesis and progression of glioma .…”
Section: Introductionmentioning
confidence: 93%